2008
DOI: 10.1101/gr.076075.108
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the genome origins and evolution of the hybrid lager yeast Saccharomyces pastorianus

Abstract: Inter-specific hybridization leading to abrupt speciation is a well-known, common mechanism in angiosperm evolution; only recently, however, have similar hybridization and speciation mechanisms been documented to occur frequently among the closely related group of sensu stricto Saccharomyces yeasts. The economically important lager beer yeast Saccharomyces pastorianus is such a hybrid, formed by the union of Saccharomyces cerevisiae and Saccharomyces bayanus-related yeasts; efforts to understand its complex ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
391
0
5

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 258 publications
(425 citation statements)
references
References 51 publications
20
391
0
5
Order By: Relevance
“…Lager strains are allopolyploid hybrids of Saccharomyces cerevisiae and a Saccharomyces bayanus-like yeast 15,53 that was recently identified as Saccharomyces eubayanus sp. nov. 44 .…”
Section: Flo Genotypes and Phenotypes In Brewer's Yeast Strainsmentioning
confidence: 99%
“…Lager strains are allopolyploid hybrids of Saccharomyces cerevisiae and a Saccharomyces bayanus-like yeast 15,53 that was recently identified as Saccharomyces eubayanus sp. nov. 44 .…”
Section: Flo Genotypes and Phenotypes In Brewer's Yeast Strainsmentioning
confidence: 99%
“…At any rate, it is obvious that array-CGH showed that the genotypes of meiotic segregants possessing both Lg-FLO1 and ILF1 had an increased copy number of the right end of SC-type chromosome VIII. Previous studies 1,2,12 reported that aneuploidy was also observed among bottom fermenting yeast strains. Most meiotic segregants have wort fermentability and are therefore valuable for the brewing industry.…”
Section: Discussionmentioning
confidence: 89%
“…Usually these complex genomes are tetraploid, which may result from the fusion of diploid parental strains or from duplication of the genetic information after the original cell fusion. Analysis on lager yeast genomes revealed other changes such as chromosome loss and/or duplications, likely due to human selection of relevant phenotypes [33,34]. In reference [34] lager yeast genomes were analysed and classified in two groups.…”
Section: Yeast Physiologymentioning
confidence: 99%
“…Analysis on lager yeast genomes revealed other changes such as chromosome loss and/or duplications, likely due to human selection of relevant phenotypes [33,34]. In reference [34] lager yeast genomes were analysed and classified in two groups. In group I, cells present one S. cerevisiae genome equivalent and, in group II, cells present two S. cerevisiae genome equivalents.…”
Section: Yeast Physiologymentioning
confidence: 99%
See 1 more Smart Citation